Enhancement of Work Culture for Quality Lecturer Performance: Empirical Study - Safrudin, Safrudin; Ghazali, Al; Don Bosco Doho, Yohannes; Ali, Moh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine whether there is an influence of work culture on the performance of lecturers at Poltekes Kemenkes III Jakarta. This study uses a quantitative approach through survey methods. The population sample is lecturers in four Departments of Health Polytechnic III Jakarta. This study indicates that work culture has a positive and significant influence on the performance of lecturers at Poltekkes Kemenkes III Jakarta. This is concluded because, from the hypothesis, the regression equation is obtained: Y = 50,135 + 0,753 X 1, which means the constant value is 50,135. From these equations, lecturer assignments can be predicted if the work culture values. The value of b = 0.753 means that the lecturer's task performance variable will increase by 75.3% if the work culture value increases by 1%. From the results of statistical tests, there is a significant relationship between workplace culture and the lecturer's task performance (p = 0.000). Moreover, the results of hypothesis testing show that the results of t arithmetic 4.651 are greater than t table 1.99 with a path coefficient of 0.365, stating that Ho is rejected and H1 is accepted.